Fikih Hukum Perbankan - Miftahul ulum (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2016)
A banking law should be based on the ideology that determines the purposes and principles. Similarly, banking law which naturally has the purpose and principles laid down by Allah and His Messenger. However, banking law studies not only see the purpose and principles of a particular, but also analyzes the behavior of economic agents in an effort to achieve their respective goals. The principles outlined by Islam always flexible. However, the atmosphere of social and environmental change over the circulation of the times. Therefore, an assessment of the banking laws and signs in the agency should consider it important to change the environment that is in place and time. Many writers of Islamic economics tends to focus on certain aspects without giving proper attention to other aspects.